Impact of Information Technology on the HR Practices in the Public Sector: Evidence from the Republic of Kosovo - HOTI, Hamdi; HOTI, Arbër H.; KURHASKU, Edisona (European Journal of Sustainable Development, 2021)
Nowadays, people are the most difficult beings to manage due to their complexity and complex nature. Human Resources in the public sector are structures that we must provide impartial treatment, ethical standards, and promote a value-based system. Human Resource Management (HRM) plays an important role in the development of a country, and in particular, in the implementation of strategic activities for the civil service in Public Administration. Recently, Information Technology (IT) has impacted all actions of society, as well as organizational processes including HRM processes and practices. Currently, Information Technology is making great changes, starting from the fact that it is impacting the public sector workers to attend training, in order for them to acquire different skills such as using IT developments, gaining new knowledge, skills, and using programs in different fields where more productive and profitable results are obtained. In this research paper, we have used two statistical extraction techniques which are OneWay ANOVA and Chi Square, which show that there is no difference between groups in the acquisition of the institution's policies, and also expresses the significance of the relationship between the main issues of active employees in developing knowledge in the use of IT in the public sector.